ILLNESS PERCEPTION AND QUALITY OF LIFE IN HIGH-RISK PREGNANCIES - Macura, Maja (Medicinski podmladak, 2024)
Abstract Illness perception can be considered as mental representation and personal experience that the patient has about their illness, and it can be measured using original and validated illness perception questionnaires. Health related quality of life (HRQoL) is a measure of person’s satisfaction with their physical and mental health, an important element of which is the illness perception. Given that pregnant women represent a particularly vulnerable category, it can be considered that pregnancy has an impact on the quality of life, especially in the case of pregnant women with pathological pregnancies. Bearing this in mind, the perception of illness in pregnancy can have a significant impact on the quality of life of pregnant women, especially in high-risk pregnancies.